Nucleation and Growth of Calcium Carbonate with Controllable Polymorphs on Solid Templates - Chen, Tian-Hua; Han, Zhi-Wu; Lu, Fei (Asian Journal of Chemistry, 2012)
Controlling crystal polymorphs and crystal size is a highly important issue in many biomedical applications. In this study, Au and Si substrates were used as solid templates to control the growth of calcium carbonate (CaCO3) crystals. The obtained CaCO3 composite was characterized by X-ray powder diffraction, scanning electron microscopy and Fourier transform infrared spectroscopy. Results show that the solid materials can serve as templates for growing different CaCO3 crystal polymorphs. Vaterite and calcite polymorphs co-form on the template because of the presence of silanol (OH) groups in the Si substrate. Aragonite polymorphs form on the Au substrate. The possible mechanism of interaction between the template and CaCO3 growth is discussed. Results suggest that template properties are important factors in controlling crystal polymorphs.